Ceibapentandra (L.) Gaertn (Kapok) Seed Fibre as a Recycled Paper Reinforcement Pulp - Leh, Cheu Peng; Junidah, Lamaming; Tan, Wen Ping; Goh, Choon Fu; Mohamad Haafiz, Mohamad Kassim; Rokiah, Hashim (Springer Nature, 2021)
The kapok (Ceibapentandra (L.) Gaertn) seed fbre is unicellular with length up to 35 mm, however, it is covered by a hydrophobic waxy layer that limits its application in paper production. In this study, the efect of various pulping methods namely mechanical, chemi-mechanical, semichemical and chemical pulping on kapok fbre properties was investigated. Each kapok pulp was then blended with the secondary fbre recovered from kraftliner board for handsheet making to examine their reinforcing ability on strength properties. The results showed that kapok mechanical pulps (with and without dewaxing (5% (v/v) diluted detergent) and chemimechanical pulp were unable to improve the strength properties of the handsheet. Kapok pulps chemically treated with 18–25% of sodium hydroxide gave a better efect on handsheet strength properties whilst fbre treated with 20% sodium hydroxide showing the highest increment. Although the reinforcing efect of the 4% native cooked starch was slightly higher than that of the 10% kapok pulp blended in recycled paper, the recycling potential of the latter was better as all strength properties retained unchanged after recycling. The fndings indicated that kapok chemical pulp is a promising reinforcing fbre source with superior recycling potential.